Nanocrystalline magnetically soft alloy and preparation method and application thereof

By introducing rare earth metals and phosphorus into iron-based nanocrystalline soft magnetic alloys, their chemical composition and heat treatment process are optimized, and problems of low high-frequency magnetic permeability and excessive growth of crystal nuclei are solved, and nanocrystalline soft magnetic alloys with high saturation magnetic induction strength, low coercivity and high-frequency magnetic permeability are achieved.

CN119763970APending Publication Date: 2025-04-04CHINA ELECTRIC POWER RESEARCH INSTITUTE CO LTD +1

Patent Information

Application Number
CN202510050550.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing iron-based nanocrystalline soft magnetic alloy has low magnetic permeability at high frequencies, which is difficult to meet the application needs of high-frequency devices. At the same time, the crystal nucleus is prone to excessive growth during the heat treatment process, resulting in deterioration of soft magnetic properties.

Method used

Nano-crystal soft magnetic alloys using Fe, Si, B, Nb, Cu, P and rare earth metals Nd and/or Sm are used. Rare earth metals are enriched at the junction of ordered phases and disordered phases, increasing ferromagnetic coupling exchange, improving magnetic induction strength and high-frequency magnetic permeability; the addition of P improves amorphous formation ability and avoids surface crystallization; by controlling the amount of rare earth metals and P, the magnetic properties of the alloy are optimized.

Benefits of technology

The nanocrystalline soft magnetic alloy has achieved a magnetic permeability of more than 42,000 at 100kHz, a saturated magnetic induction strength of more than 1.75T, and a coercive force as low as 0.8A/m, and has excellent high-frequency soft magnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005239833540000101
    Figure BDA0005239833540000101
Patent Text Reader

Abstract

The invention belongs to the technical field of magnetic functional materials, and particularly relates to a nanocrystalline magnetically soft alloy and a preparation method and application thereof. The invention provides a nanocrystalline soft magnetic alloy which comprises the following chemical components: Fe, Si, B, Nb, Cu, P and rare earth metal, and the rare earth metal is selected from at least one of Nd and Sm. According to the nanocrystalline magnetically soft alloy, a proper amount of rare earth metal is added, the ferromagnetic coupling exchange effect between ordered phases of the nanocrystalline magnetically soft alloy is improved, so that the magnetic induction intensity and the high-frequency magnetic conductivity of the nanocrystalline magnetically soft alloy are both improved, the magnetic conductivity of the nanocrystalline magnetically soft alloy at 100 kHz can reach 42000 or above, and the high-frequency magnetic conductivity of the nanocrystalline magnetically soft alloy at 100 kHz can reach 42000 or above. Meanwhile, the saturation flux density reaches up to 1.75 T or above, and the coercive force is as low as 0.8 A / m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic functional materials, and in particular relates to a nanocrystalline soft magnetic alloy and a preparation method and application thereof. Background Art

[0002] Soft magnetic alloy is an important functional material. It has high magnetic permeability and low coercivity in weak magnetic field. It is widely used in radio electronics industry, precision instruments, remote control and automatic control system. Among them, iron-based nanocrystalline alloy is a new type of soft magnetic material, which was first proposed by Yoshizawa et al. in 1988. Its standard composition is Fe 73.5 Cu1Nb3Si 13.5 B9, this alloy has the obvious advantages of high magnetic permeability, low coercivity and low loss, but its saturation magnetic induction intensity needs to be improved.

[0003] In this regard, researchers have continuously improved its composition content in order to obtain a soft magnetic alloy with excellent comprehensive performance. For example, the Chinese patent application number 201910627912.4 discloses an alloy composition, the composition expression of which is Fe a V α B b Si c P x C y Cu z , wherein 79≤a≤91at%, 5≤b≤13at%, 0≤c≤8at%, 1≤x≤8at%, 0≤y≤5at%, 0.4≤z≤1.4at%, 0<α<5at%, and 0.08≤z / x≤0.8, the iron-based nanocrystalline alloy has a coercive force of less than 20A / m and a saturation magnetic induction intensity of more than 1.65T, but its magnetic permeability is low at high frequencies (especially 100kHz), which makes it difficult to meet the application requirements of high-frequency devices such as high-frequency transformers, common-mode inductors, chokes and wireless charging modules. The Chinese patent application number 201110418631.1 discloses an iron-based nanocrystalline soft magnetic alloy, whose composition is represented by the chemical formula Fe g Si a P b C c Cu d Mn e Al fThe iron-based nanocrystalline soft magnetic alloy does not contain precious elements such as Co, Zr, Nb, and B, and has low production costs. Under the optimal crystallization annealing process conditions, the saturation magnetic induction intensity is as high as 1.71T, and the coercive force is as low as 0.9A / m, which has excellent soft magnetic properties. However, the alloy tends to grow excessively during the heat treatment process, which deteriorates the soft magnetic properties, so the heat treatment process is required to be relatively high.

[0004] Therefore, it is of great significance to develop nanocrystalline soft magnetic alloys with high frequency, high magnetic induction intensity and low coercivity. Summary of the invention

[0005] In view of this, the present invention provides a nanocrystalline soft magnetic alloy and a preparation method and application thereof. The nanocrystalline soft magnetic alloy can simultaneously have high frequency, high magnetic induction intensity and low coercive force, and has a small grain size and excellent soft magnetic properties.

[0006] To solve the above technical problems, a first aspect of the present invention provides a nanocrystalline soft magnetic alloy, the chemical composition of which includes Fe, Si, B, Nb, Cu, P and rare earth metals, and the rare earth metal is selected from at least one of Nd and Sm.

[0007] The nanocrystalline soft magnetic alloy provided by the present invention comprises Fe, Si, B, Nb, Cu, P and rare earth metal Nd and / or Sm. The rare earth metal Nd and / or Sm has a 4f electronic structure and is enriched at the junction of an ordered phase and a disordered phase, thereby increasing the ferromagnetic coupling exchange effect between the ordered phases in the nanocrystalline soft magnetic alloy and improving the high magnetic induction intensity and high-frequency magnetic permeability of the nanocrystalline soft magnetic alloy; moreover, the rare earth metal Nd and / or Sm also has the effect of refining the grains, thereby weakening the pinning effect of the grains on the domain wall movement and reducing the coercive force and loss of the alloy. In addition, the addition of P can improve the amorphous forming ability of the nanocrystalline soft magnetic alloy and avoid the phenomenon of crystallization on the alloy surface.

[0008] In combination with the first aspect, the chemical formula of the nanocrystalline soft magnetic alloy is Fe a Si b B c Nb d Cu e P f M g , where M is a rare earth metal, a, b, c, d, e, f and g are all atomic percentages of the corresponding elements, and a+b+c+d+e+f+g=100, 70.4≤a≤73.8, 9.3≤b≤12.3, 8.2≤c≤9.8, 3.1≤d≤4.7, 1.2≤e≤1.6, 4.2≤f≤5.6, 0.1≤g≤1.2.

[0009] The present invention ensures that the nanocrystalline soft magnetic alloy has a higher saturation magnetic induction intensity by controlling the amount of rare earth metal. When the content of rare earth metal is higher than 1.2%, the saturation magnetic induction intensity of the nanocrystalline soft magnetic alloy will be reduced. In addition, by controlling the amount of P, the amorphous forming ability of the alloy is improved while a satisfactory saturation magnetic induction intensity can be obtained.

[0010] Preferably, the chemical formula of the nanocrystalline soft magnetic alloy is Fe a Si b B c Nb d Cu e P f M g , where M is a rare earth metal, a, b, c, d, e, f and g are all atomic percentages of the corresponding elements, and a+b+c+d+e+f+g=100, 71.2≤a≤71.7, 9.8≤b≤10.3, 8.4≤c≤8.9, 3.6≤d≤4.1, 1.4≤e≤1.5, 4.5≤f≤5.0, 0.5≤g≤0.8.

[0011] In combination with the first aspect, the grain size of the nanocrystalline soft magnetic alloy is 4-10 nm. Grains of this size can make the nanocrystalline soft magnetic alloy have high saturation magnetic induction intensity and lower coercive force, thereby ensuring the soft magnetic properties of the alloy.

[0012] Preferably, the grain size of the nanocrystalline soft magnetic alloy is 4-7 nm.

[0013] The second aspect of the present invention provides a method for preparing the above-mentioned nanocrystalline soft magnetic alloy, the steps comprising: mixing the raw materials according to the atomic percentage ratio, and sequentially performing vacuum melting, casting strip preparation and annealing heat treatment to obtain the nanocrystalline soft magnetic alloy; the vacuum melting material is specifically: adding the raw materials into a vacuum melting furnace, heating to 1350-1450°C and then melting for 20-30 minutes, and continuing to heat to 1600-1700°C and melting for at least 10 minutes to obtain an alloy ingot.

[0014] The invention obtains nanocrystalline soft magnetic alloy by mixing raw materials in proportion, performing vacuum melting, preparing casting strips and annealing heat treatment in sequence. The vacuum melting method can ensure the purity of the raw materials after melting and reduce the impurity content introduced in the preparation process.

[0015] In addition, the preparation method of the nanocrystalline soft magnetic alloy provided by the present invention adopts a staged heating method in the vacuum melting step, so that the rare earth metal is melted more fully and evenly in the metal liquid, providing a guarantee for the metal liquid to form evenly distributed and uniformly sized crystal nuclei under the high-speed rapid cooling conditions of the casting strip preparation step, thereby ensuring that the nanocrystalline soft magnetic alloy has a higher saturation magnetic induction intensity and high-frequency magnetic permeability.

[0016] By improving the alloy composition materials and the preparation method, the nanocrystalline soft magnetic alloy obtained by the present invention can achieve a magnetic permeability of more than 42,000 at 100 kHz, a saturation magnetic induction intensity of more than 1.75 T, and a coercive force as low as 0.8 A / m.

[0017] The nanocrystalline soft magnetic alloy provided by the present invention is more in line with the development trend of miniaturization and high efficiency of power electronic devices, and provides support for the rapid development of electronic technology.

[0018] In combination with the second aspect, the preparation of the cast strip is specifically as follows: after the alloy ingot is remelted, the alloy liquid is sprayed onto the surface of a high-speed rotating copper roller with a temperature of 100 to 200°C using a single-roll melt rapid quenching method, and a static magnetic field is applied between the nozzle and the copper roller along the width direction of the copper roller while making the strip to obtain an alloy cast strip.

[0019] The invention regulates the element composition and content of the alloy and simultaneously controls specific parameters in the casting strip preparation process, so that the width of the alloy casting strip obtained is 150-200 mm and the thickness is 10-14 μm.

[0020] In the process of preparing the alloy casting strip of the present invention, a static magnetic field is applied along the width direction of the copper roller, so that more atomic magnetic moments in the casting strip can be oriented along its width direction. Therefore, when the soft magnetic alloy is placed in an alternating magnetic field, the overall magnetic moment of atomic flipping is shortened, that is, the time required for the deflection of the atomic magnetic moment is shortened, the loss is reduced, and the soft magnetic alloy is ensured to have a higher high-frequency magnetic permeability.

[0021] In combination with the second aspect, the distance between the nozzle and the surface of the copper roller is 1.5-2.3 mm, and the linear speed of the copper roller is 24-28 m / s.

[0022] In combination with the second aspect, the annealing heat treatment specifically includes: applying a static magnetic field along the width direction of the alloy casting strip, and sequentially performing a first annealing treatment, a second annealing treatment and a heat preservation treatment on the alloy casting strip.

[0023] In combination with the second aspect, the first annealing treatment is: heating to 470-550°C at a rate of 15-35°C / min and then keeping warm for 40-60min; the second annealing treatment is: heating to 560-600°C at a rate of 3-8°C / min and then keeping warm for 15-30min; the insulation treatment is: when the temperature drops to 300-350°C, keeping warm for 50-70min, and then continuing to cool to room temperature.

[0024] The present invention adopts a step-by-step annealing method to eliminate the internal stress in the alloy casting strip to the maximum extent, and promotes the precipitation of nanocrystals in the amorphous matrix while obtaining smaller grains. In the cooling process, when the temperature drops to 300-350°C, it is kept warm for 50-70 minutes to ensure the full release of the internal stress and the stability of the grain size, so that the obtained soft magnetic alloy has high saturation magnetic induction intensity and high frequency and high magnetic permeability.

[0025] A third aspect of the present invention provides a nanocrystalline soft magnetic alloy or a nanocrystalline soft magnetic alloy prepared according to the preparation method of the nanocrystalline soft magnetic alloy in a high-frequency transformer, an inductor, a mutual inductor or a wireless charging.

[0026] Beneficial effects obtained by the present invention: The magnetic permeability of the nanocrystalline soft magnetic alloy provided by the present invention can reach more than 42000 at 100kHz, while the saturation magnetic induction intensity is as high as more than 1.75T, and the coercive force is as low as 0.8A / m. The nanocrystalline soft magnetic alloy provided by the present invention is more in line with the development trend of miniaturization and high efficiency of power electronic devices, and provides support for the rapid development of electronic technology. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0028] Those skilled in the art will appreciate that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined.

[0029] In recent years, nanocrystalline soft magnetic alloys, as a material with excellent soft magnetic properties, have been widely used in the fields of electronics, electricity, and communications. However, despite its broad application prospects, there are still some technical problems that need to be solved at this stage. For example, how to further improve its key performance indicators such as magnetic permeability, saturation magnetization intensity, and magnetic loss through material design and process improvement is the key to promoting the application of this material to a higher level.

[0030] To this end, some studies have attempted to solve the above problems by changing the material composition. For example, the related prior art introduced in the background technology (Chinese patent application number 201910627912.4 discloses an alloy composition, the expression of which is the composition expression of Fe a Vα B b Si c P x C y Cu z , wherein 79≤a≤91at%, 5≤b≤13at%, 0≤c≤8at%, 1≤x≤8at%, 0≤y≤5at%, 0.4≤z≤1.4at%, 0<α<5at%, and 0.08≤z / x≤0.8, the iron-based nanocrystalline alloy has a coercive force of less than 20A / m and a saturation magnetic induction intensity of more than 1.65T, but its magnetic permeability is low at high frequencies (especially 100kHz), which makes it difficult to meet the application requirements of high-frequency devices such as high-frequency transformers, common-mode inductors, chokes and wireless charging modules. The Chinese patent application number 201110418631.1 discloses an iron-based nanocrystalline soft magnetic alloy, whose composition is represented by the chemical formula Fe g Si a P b C c Cu d Mn e Al f The iron-based nanocrystalline soft magnetic alloy does not contain precious elements such as Co, Zr, Nb, and B, and has low production costs. Under the optimal crystallization annealing process conditions, the saturation magnetic induction intensity is as high as 1.71T, and the coercive force is as low as 0.9A / m, which has excellent soft magnetic properties.

[0031] However, the alloy of the above composition tends to grow excessively during heat treatment, resulting in poor soft magnetic properties. In view of this, the present invention provides a nanocrystalline soft magnetic alloy and a preparation method and application thereof, which can simultaneously have high frequency, high magnetic induction intensity and low coercivity, and has a small grain size and excellent soft magnetic properties.

[0032] If no specific experimental steps or conditions are specified in the following examples of the present invention, the conventional experimental steps or conditions described in the literature in the art can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0033] Example 1

[0034] This embodiment provides a nanocrystalline soft magnetic alloy, whose chemical composition expression is Fe 71.2 Si 9.8 B 8.9 Nb 3.6 Cu 1. 4P 4.5 Nd 0.6 The preparation steps of the nanocrystalline soft magnetic alloy include:

[0035] Vacuum melt: Mix the iron raw material, silicon raw material, ferroboron alloy, ferroniobium alloy, copper raw material, phosphorus raw material and neodymium iron alloy in the above proportions, add them into the crucible of the vacuum induction melting furnace, evacuate to below 1.2Pa, heat to 1400℃ and melt for 25min, then continue to heat to 1650℃ and melt for 10min. After cooling down, pour the smelted metal liquid into a cooling mold to cool it down to obtain an alloy ingot with uniform composition.

[0036] Preparation of cast strip: After the alloy ingot is remelted to a liquid state, it is transferred to a tundish, and the alloy liquid is sprayed onto the surface of a high-speed rotating copper roller at a temperature of 150°C using a single-roll melt rapid quenching method. While making the strip, a static magnetic field with a magnetic induction intensity of 0.1 T is applied between the nozzle and the copper roller along the width direction of the copper roller. The distance between the nozzle and the surface of the copper roller is 2.0 mm, and the linear speed of the copper roller is 26 m / s to obtain an alloy cast strip.

[0037] Annealing heat treatment: the obtained alloy casting strip is cut and rolled into a circular magnetic core with a certain inner diameter, outer diameter and height by a magnetic core winding machine, and then placed in a vacuum magnetic field heat treatment furnace, evacuated, and a static magnetic field with a magnetic induction intensity of 0.2T is applied along the width direction of the alloy casting strip. The temperature is increased to 500℃ at a rate of 20℃ / min and then kept warm for 50min, and then increased to 580℃ at a rate of 5℃ / min and then kept warm for 20min; then the heat treatment furnace is closed to cool down. When the temperature drops to 300℃, the heat treatment furnace is opened and kept warm at 300℃ for 60min, and then continued to cool to room temperature.

[0038] Example 2

[0039] This embodiment provides a nanocrystalline soft magnetic alloy, whose chemical composition expression is Fe 70.4 Si 12.3 B 8.2 Nb 3.1 Cu 1. 6P 4.2 Sm 0.2 The preparation steps of the nanocrystalline soft magnetic alloy include:

[0040] Vacuum melting material: Mix the iron raw material, silicon raw material, ferroboron alloy, ferroniobium alloy, copper raw material, phosphorus raw material and samarium iron alloy in the above proportions, add them into the crucible of the vacuum induction melting furnace, evacuate to below 1.2Pa, heat to 1350℃ and melt for 30min, then continue to heat to 1600℃ and melt for 30min. After cooling down, pour the smelted metal liquid into a cooling mold to cool it down to obtain an alloy ingot with uniform composition.

[0041] Preparation of cast strip: After the alloy ingot is remelted to a liquid state, it is transferred to a tundish, and the alloy liquid is sprayed onto the surface of a high-speed rotating copper roller at a temperature of 100°C using a single-roll melt rapid quenching method. While making the strip, a static magnetic field with a magnetic induction intensity of 0.1 T is applied between the nozzle and the copper roller along the width direction of the copper roller. The distance between the nozzle and the surface of the copper roller is 1.5 mm, and the linear speed of the copper roller is 24 m / s to obtain an alloy cast strip.

[0042] Annealing heat treatment: the obtained alloy casting strip is cut and rolled into a circular magnetic core with a certain inner diameter, outer diameter and height by a magnetic core winding machine, and then placed in a vacuum magnetic field heat treatment furnace, evacuated, and a static magnetic field with a magnetic induction intensity of 0.2T is applied along the width direction of the alloy casting strip. The temperature is increased to 470℃ at a rate of 15℃ / min and then kept warm for 60min, and then increased to 560℃ at a rate of 3℃ / min and then kept warm for 30min; then the heat treatment furnace is closed to cool down. When the temperature drops to 350℃, the heat treatment furnace is opened and kept warm at 350℃ for 50min, and then continued to cool to room temperature.

[0043] Example 3

[0044] This embodiment provides a nanocrystalline soft magnetic alloy, whose chemical composition expression is Fe 73.5 Si 9.3 B 8.3 Nb 3.2 Cu 1. 2P 4.2 Nd 0.1 Sm 0.2 The preparation steps of the nanocrystalline soft magnetic alloy include:

[0045] Vacuum melt: Mix the iron raw material, silicon raw material, ferroboron alloy, ferroniobium alloy, copper raw material, phosphorus raw material, neodymium iron alloy and samarium iron alloy in the above proportions, add them into the crucible of the vacuum induction melting furnace, evacuate to below 1.2 Pa, heat to 1450℃ and melt for 20 minutes, then continue to heat to 1700℃ and melt for 12 minutes. After cooling down, pour the smelted metal liquid into a cooling mold to cool it down to obtain an alloy ingot with uniform composition.

[0046] Preparation of cast strip: After the alloy ingot is remelted to a liquid state, it is transferred to a tundish, and the alloy liquid is sprayed onto the surface of a high-speed rotating copper roller at a temperature of 200°C using a single-roll melt rapid quenching method. While making the strip, a static magnetic field with a magnetic induction intensity of 0.1 T is applied between the nozzle and the copper roller along the width direction of the copper roller. The distance between the nozzle and the surface of the copper roller is 2.3 mm, and the linear speed of the copper roller is 28 m / s to obtain an alloy cast strip.

[0047] Annealing heat treatment: the obtained alloy casting strip is cut and rolled into a circular magnetic core with a certain inner diameter, outer diameter and height by a magnetic core winding machine, and then placed in a vacuum magnetic field heat treatment furnace, evacuated, and a static magnetic field with a magnetic induction intensity of 0.2T is applied along the width direction of the alloy casting strip. The temperature is increased to 550℃ at a rate of 35℃ / min and then kept warm for 40min, and then increased to 600℃ at a rate of 8℃ / min and then kept warm for 15min; then the heat treatment furnace is closed to cool down. When the temperature drops to 350℃, the heat treatment furnace is opened and kept warm at 300℃ for 70min, and then continued to cool to room temperature.

[0048] Example 4

[0049] This embodiment provides a nanocrystalline soft magnetic alloy, whose chemical composition expression is Fe 70.7 Si 9.9 B 8.4 Nb 4.1 Cu 1. 3P 4.2 Nd 1.2 Sm 0.2 The preparation steps of the nanocrystalline soft magnetic alloy include:

[0050] Vacuum melt: Mix the iron raw material, silicon raw material, ferroboron alloy, ferroniobium alloy, copper raw material, phosphorus raw material, neodymium iron alloy and samarium iron alloy in the above proportions, add them into the crucible of the vacuum induction melting furnace, evacuate to below 1.2 Pa, heat to 1380℃ and melt for 25min, then continue to heat to 1670℃ and melt for 16min. After cooling, pour the smelted metal liquid into a cooling mold to cool it down to obtain an alloy ingot with uniform composition.

[0051] Preparation of cast strip: After the alloy ingot is remelted to a liquid state, it is transferred to a tundish, and the alloy liquid is sprayed onto the surface of a high-speed rotating copper roller at a temperature of 180°C using a single-roll melt rapid quenching method. While making the strip, a static magnetic field with a magnetic induction intensity of 0.1 T is applied between the nozzle and the copper roller along the width direction of the copper roller. The distance between the nozzle and the surface of the copper roller is 1.8 mm, and the linear speed of the copper roller is 27 m / s to obtain an alloy cast strip.

[0052] Annealing heat treatment: the obtained alloy casting strip is cut and rolled into a circular magnetic core with a certain inner diameter, outer diameter and height by a magnetic core winding machine, and then placed in a vacuum magnetic field heat treatment furnace, evacuated, and a static magnetic field with a magnetic induction intensity of 0.2T is applied along the width direction of the alloy casting strip. The temperature is raised to 490℃ at a rate of 22℃ / min and then kept warm for 55min, and then raised to 580℃ at a rate of 6℃ / min and then kept warm for 26min; then the heat treatment furnace is closed for cooling. When the temperature drops to 330℃, the heat treatment furnace is opened and kept warm at 330℃ for 65min, and then continued to cool to room temperature.

[0053] Comparative Example 1

[0054] This comparative example provides a nanocrystalline soft magnetic alloy, whose chemical composition expression is Fe 71.2 Si 9.8 B 8.9 Nb 3.6 Cu 1. 4P 4.5 Nd 0.6 The preparation steps of the nanocrystalline soft magnetic alloy include:

[0055] Vacuum melt: Mix the iron raw material, silicon raw material, ferroboron alloy, ferroniobium alloy, copper raw material, phosphorus raw material and neodymium iron alloy in the above proportions, add them into the crucible of the vacuum induction melting furnace, evacuate to below 1.2Pa, heat to 1400℃ and melt for 25min, then continue to heat to 1650℃ and melt for 10min. After cooling down, pour the smelted metal liquid into a cooling mold to cool it down to obtain an alloy ingot with uniform composition.

[0056] Preparation of cast strip: After the alloy ingot is remelted to a liquid state, it is transferred to a tundish, and the alloy liquid is sprayed onto the surface of a high-speed rotating copper roller at a temperature of 150°C using a single-roll melt rapid quenching method. While making the strip, a static magnetic field with a magnetic induction intensity of 0.1 T is applied between the nozzle and the copper roller along the width direction of the copper roller. The distance between the nozzle and the surface of the copper roller is 2.0 mm, and the linear speed of the copper roller is 26 m / s to obtain an alloy cast strip.

[0057] Annealing heat treatment: the obtained alloy casting strip is cut and rolled into a circular magnetic core with a certain inner diameter, outer diameter and height by a magnetic core winding machine, and then placed in a vacuum magnetic field heat treatment furnace, evacuated, and a static magnetic field with a magnetic induction intensity of 0.2T is applied along the width direction of the alloy casting strip. The temperature is raised to 500℃ at a rate of 20℃ / min and then kept warm for 50min, and then raised to 580℃ at a rate of 5℃ / min and then kept warm for 20min; then the heat treatment furnace is closed and cooled to room temperature.

[0058] Comparative Example 2

[0059] This comparative example provides a nanocrystalline soft magnetic alloy, whose chemical composition expression is Fe 71.8 Si 9.8 B 8.9 Nb 3.6 Cu 1.4 P 4.5 The composition of the nanocrystalline soft magnetic alloy differs from that of Example 1 in that no rare earth metal is added. The preparation steps and parameters are the same as those in Example 1 and are not described in detail.

[0060] Test Example 1

[0061] The grain size of the nanocrystalline soft magnetic alloys obtained in Examples 1 to 4 and Comparative Examples 1 to 2 was measured by transmission electron microscopy, and the coercive force, saturation magnetic induction intensity, and magnetic permeability at a frequency of 100 kHz were measured. The test results of various properties are shown in Table 1.

[0062] Table 1

[0063]

[0064] As can be seen from Table 1, the average grain size of the nanocrystalline soft magnetic alloy provided by the present invention is 10nm or less, which is smaller than the grain size of the existing nanocrystalline soft magnetic alloy, so that the magnetic permeability can still reach more than 40000 under high-frequency conditions. Compared with Example 1, the grain size of the nanocrystalline soft magnetic alloy obtained in Comparative Example 1 is significantly increased, the high-frequency magnetic permeability is significantly reduced, and the loss is increased, indicating that the step-by-step cooling method adopted in the heat treatment stage can control the grains to be in a smaller size, thereby ensuring the high-frequency magnetic permeability and low loss of the nanocrystalline soft magnetic alloy. The coercive force of the nanocrystalline soft magnetic alloy obtained in Comparative Example 2 is greater, and the saturation magnetic induction intensity, high-frequency magnetic permeability and loss are all increased, indicating that the introduction of rare earth metals Nd or Sm can greatly reduce the coercive force and loss of the nano soft magnetic alloy, while improving the saturation magnetic induction intensity and high-frequency magnetic permeability.

[0065] In summary, under the condition of a magnetic permeability of 100kHz, the magnetic permeability of the nanocrystalline soft magnetic alloy provided by the present invention can reach more than 42000, the saturation magnetic induction intensity can reach more than 1.75T, and the coercive force is as low as 0.8A / m, which has good comprehensive electromagnetic properties. In addition, the nanocrystalline soft magnetic alloy provided by the present invention is more in line with the development trend of miniaturization and high efficiency of power electronic devices, providing support for the rapid development of electronic technology.

[0066] What is described above is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A nanocrystalline soft magnetic alloy, characterized in that: The chemical composition includes Fe, Si, B, Nb, Cu, P and rare earth metals, and the rare earth metal is selected from at least one of Nd and Sm.

2. The nanocrystalline soft magnetic alloy according to claim 1, characterized in that: The chemical formula of the nanocrystalline soft magnetic alloy is Fe a Si b B c Nb d Cu e P f M g , where M is a rare earth metal, a, b, c, d, e, f and g are all atomic percentages of the corresponding elements, and a+b+c+d+e+f+g=100, 70.4≤a≤73.8, 9.3≤b≤12.3, 8.2≤c≤9.8, 3.1≤d≤4.7, 1.2≤e≤1.6, 4.2≤f≤5.6, 0.1≤g≤1.

2.

3. The nanocrystalline soft magnetic alloy according to claim 2, characterized in that: 71.2≤a≤71.7, 9.8≤b≤10.3, 8.4≤c≤8.9, 3.6≤d≤4.1, 1.4≤e≤1.5, 4.5≤f≤5.0, 0.5≤g≤0.

8.

4. The nanocrystalline soft magnetic alloy according to any one of claims 1 to 3, characterized in that: The grain size of the nanocrystalline soft magnetic alloy is 4-10 nm.

5. The method for preparing a nanocrystalline soft magnetic alloy according to any one of claims 1 to 4, characterized in that the steps include: The raw materials are mixed according to the atomic percentage ratio, and vacuum melting, strip casting and annealing heat treatment are performed in sequence to obtain a nanocrystalline soft magnetic alloy; The vacuum melting material is specifically: adding various raw materials into a vacuum melting furnace, heating to 1350-1450° C. and then melting for 20-30 minutes, and then continuing to heat to 1600-1700° C. and melting for at least 10 minutes to obtain an alloy ingot.

6. The method for preparing a nanocrystalline soft magnetic alloy according to claim 5, characterized in that: The casting strip is prepared specifically as follows: after remelting the alloy ingot, the alloy liquid is sprayed onto the surface of a high-speed rotating copper roller at a temperature of 100 to 200°C using a single-roll melt rapid quenching method, and a static magnetic field is applied between the nozzle and the copper roller along the width direction of the copper roller while making the strip, to obtain an alloy casting strip.

7. The method for preparing a nanocrystalline soft magnetic alloy according to claim 6, characterized in that: The distance between the nozzle and the surface of the copper roller is 1.5-2.3 mm, and the linear speed of the copper roller is 24-28 m / s.

8. The method for preparing a nanocrystalline soft magnetic alloy according to claim 5, characterized in that: The annealing heat treatment specifically includes: applying a static magnetic field along the width direction of the alloy casting strip, and sequentially performing a first annealing treatment, a second annealing treatment and a heat preservation treatment on the alloy casting strip.

9. The method for preparing a nanocrystalline soft magnetic alloy according to claim 8, characterized in that: The first annealing treatment is: heating to 470-550°C at a rate of 15-35°C / min and then keeping warm for 40-60min; the second annealing treatment is: heating to 560-600°C at a rate of 3-8°C / min and then keeping warm for 15-30min; the insulation treatment is: when the temperature drops to 300-350°C, keeping warm for 50-70min, and then continuing to cool to room temperature.

10. Use of the nanocrystalline soft magnetic alloy according to any one of claims 1 to 4 or the nanocrystalline soft magnetic alloy prepared by the preparation method of the nanocrystalline soft magnetic alloy according to any one of claims 5 to 9 in high-frequency transformers, inductors, mutual inductors or wireless charging.

Citation Information

Patent Citations

  • Iron-based nanocrystalline magnetically soft alloy

    CN102412045B

  • Alloy composition, fe-based nanocrystalline alloy and manufacturing method therefor, and magnetic component

    CN110819914A

Cited By

  • High-permeability nanocrystalline soft magnetic alloy, strip and preparation method and application of high-permeability nanocrystalline soft magnetic alloy

    CN120340986A

  • A high magnetic permeability nanocrystalline soft magnetic alloy, strip, and preparation method and application thereof

    CN120340986B

  • High-squareness-ratio amorphous alloy and preparation method thereof

    CN121826554A